Director of GeoNet needs to be heard - Gaston, Nicola (New Zealand Science Review, 2017)
The New Zealand Association of Scientists (NZAS) is alarmed at reports that the Acting Civil Defence Minister, Gerry Brownlee, is ‘furious with GeoNet comments’ made by the service’s Director, Dr Ken Gledhill.‘GeoNet is an important service in which all New Zealanders have an interest’, said NZAS President Craig Stevens, ‘and if Dr Gledhill can suggest cost-effective measures to make New Zealand safer, he should be encouraged to say so, and publicly.’ There have been other media reports that have questioned the quality of the response, and these concerns should rightly be taken on board by all involved, including the scientific community. It is of deep concern that the Government response is to vilify voices that seek to encourage us to learn from a post-mortem of events. The magnitude 7.8 Kaikoura earthquake was unique amongst the many events GeoNet has responded to in recent years, because it produced a significant tsunami immediately along the New Zealand coastline. This tsunami potentially threatened population centres, especially the Wellington region, within a short time. The Association calls on the Government to be responsible in its discussions with the science agencies, such as GNS Science, that support critical government services, such as the Ministry of Civil Defence and Emergency Management. To maximise the safety of New Zealanders, the Association recommends that the Government avoid actions that might lead to the repression of scientific advice to the public.